Design and simulation of DC-DC buck-boost converter with voltage source inverter using MATLAB/Simulink for BLDC motor drives - T., Sithananthan; Bakar, A. A.; Poad, H.M.; Salimin, S. (2024)
The brushless DC (BLDC) motor is frequently employed in various applications, as it has excellent features compared with those of the conventional brushed DC motor. Furthermore, the BLDC motor is electrically commuted by power switches, resulting in higher reliability, more significant dynamic response, and longer operating life. A three-phase voltage source inverter (VSI) is fed to the BLDC motor to operate, as it has better performance at low speeds. The inverter operates in 120° and 180° conduction modes. In this paper, a DC-DC buck-boost converter was implemented to act as thestep-up or step-down transformer for the system, as it offershigh efficiency across extensive input and output voltage ranges. A simulation using MATLAB/Simulink software was carriedout with different duty cycles, and the result was analyzed.Based on the results obtained, the overshoot percentage was5.22% with a settling time of 0.042s